Analysis of Stunting Incidence and its Influencing Factors in Banggle Village - Rahayu, Elvidya; Mayta Sari Dwianggimawati (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2022)
Stunting is an important problem. This is because it is very influential on the future development of the nation starting from the growth of its children. Stunting in children is a chronic nutritional problem due to inadequate nutritional intake in the long term combined with infectious diseases in children and environmental problems. Stunting needs special attention because it can increase the risk of death in children, as well as hinder the physical and mental development of children. The method used in this research is a quantitative method with case control study. The population in this study is all children under five aged 1-5. The research location is in Bangggle Village, Kanigoro District, Blitar Regency. The time of the study was July – August 2021. The sample of this study was 84 respondents using the Purposive Sampling technique with a total of 42 case respondents and 42 control respondents. The statistical test used was the chi square test. family income, mother's occupation, history of basic immunization and history of ARI and diarrhea. Meanwhile, the results of statistical tests for other variables can be concluded that there is a relationship between birth weight, mother's education, history of exclusive breastfeeding, energy and protein intake and the incidence of stunting (p=<0.05).